Effects of explosive muscular power training on physical and complex skill abilities in basketball players - Abd Elaziz Mohamed, A. D. (World Journal of Sport Sciences, 2012)
The purpose of this study was to determine the effects of a 6-week explosive muscular power training program on physical abilities (legs muscle power, agility, receiving ball and jump shoot as a complex skill) and correlation between receiving ball and jump shoot as a complex skill and physical abilities. The researcher used the experimental method on a sample chosen by the intentional method from El-shobban El-moslemen sport club U 16 of 20 male players. Results support that improvements in physical abilities and receiving ball and jump shoot as a complex skill can occur in as little as 6-weeks of explosive muscular power training which can be useful during the last preparatory phase before in-season competition for athletes.